SOME ISSUES OF REGULATION OF CYBERSPORT AND BUSINESS ACTIVITIES IN IT (TSUL LEGAL REPORT, 2026)
This article aims to consider some issues of regulation of the cybersport industry, to analyze its fragmentation and diversity, giving examples of the most popular games, the main parties involved in this industry: players, teams, organizations, leagues, publishers. The article attempts to determine the legal framework and regulation of e-sports based on international experience. The author, considering e-sports as a business, notes an unusually accelerated product life cycle, the opportunity to work on a franchise, a variety of potential business partners, as well as the prospects for investing in this industry. Thus, it is concluded that cybersport is a new phenomenon and is currently a developing area of sports. This sport has its supporters and opponents; there are those who does not classify cybersport as a sport as such. However, today e-sports is a powerful industry that is actively developing around the world, brings significant income, and shows the need for comprehensive legal regulation.